Artificial Intelligence Enabled Personalised Assistive Tools to Enhance Education of Children with Neurodevelopmental Disorders—A Review - Prabal Datta Barua; Jahmunah Vicnesh; Raj Gururajan; Shu Lih Oh; Elizabeth Palmer; Muhammad Mokhzaini Azizan; Nahrizul Adib Kadri; U Rajendra Acharya (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA